Species effect on decay resistance of wood exposed to exterior conditions above the ground in Spain - Conde-García, M.; Conde-García, M; Fernández-Golfín, J.I. (Materiales de Construcción, 2021)
The objective of this study is to evaluate the effect of the species on the biological resistance of wood against decay and to propose corrective values of the critical dose. To evaluate the species effect, the evolution of the number of days per year with moisture content exceeding 18% was assessed in flat sawn 20x100x750 mm3 test samples of Laricio, Scots and Radiata pines and also of Norway spruce, Eucalypt (globulus) and sweet chestnut during the years 2016, 2017 and 2018, exposed at seven locations in Spain with the most representative Spanish climates. A value of 1.0 is proposed for the four conifers, 2.51 for the Eucalypt and 1.84 for the Sweet chestnut. As regards the species effect it was not possible to separate that corresponding to the different wetting/releasing ability of each species and that of their crack susceptibility, both aspects having to be evaluated together as “species factor”.